Manajemen Administrasi dan Keuangan di Desa Bajo, Kecamatan Tilamuta, Kabupaten Boalemo - Baderan, Umar Sako; Lantowa, Felmi D.; Makur, Dharmawaty S.; Idji, Abdurrahaman (Penerbit Goodwood, 2025)
Purpose: This community service aimed to improve the capacity of village apparatus and micro, small, and medium enterprises (MSMEs) in managing village administration and financial reporting based on accountability and transparency principles. Methodology/approach: The activity was conducted in Bajo Village, Tilamuta Sub-district, Boalemo Regency. A participatory workshop method was applied, involving lectures, discussions, and hands-on practice. The materials covered included village administrative document management, simple bookkeeping, and financial report preparation in accordance with applicable regulations. The program utilized printed materials, Microsoft Excel for bookkeeping exercises, and interactive group discussions to enhance participants’ understanding. Results/findings: The activity improved participants’ knowledge, technical skills, and awareness regarding good governance practices. Village apparatus became more capable of preparing administrative records and cash-based accrual financial reports. Participants also demonstrated a positive shift in attitude towards the importance of transparency and accountability in financial management. Conclusion: The activity enhanced village governance capacity, showing that training and assistance are key to improving accountability and professionalism in administrative and financial management. Limitations: The program was limited in scope to basic administrative and financial management and did not cover advanced digital tools due to limited digital literacy and infrastructure at the village level. Contribution: This activity contributes to the field of public administration, particularly in strengthening local governance at the village level. It supports capacity building for rural institutions and provides a practical model for other community engagement initiatives in administrative and financial training.